2017
DOI: 10.1038/s41598-017-03450-0
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Quantification of Placental Insufficiency by BOLD MRI: A Human Study

Abstract: Fetal health is critically dependent on placental function, especially placental transport of oxygen from mother to fetus. When fetal growth is compromised, placental insufficiency must be distinguished from modest genetic growth potential. If placental insufficiency is present, the physician must trade off the risk of prolonged fetal exposure to placental insufficiency against the risks of preterm delivery. Current ultrasound methods to evaluate the placenta are indirect and insensitive. We propose to use Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 40 publications
(41 reference statements)
1
65
1
Order By: Relevance
“…In addition, three animal studies described changes in placental signal intensity during maternal hypoxia, normoxic hypercapnia and injection of a vasoconstrictor. Human studies were performed at both 1.5 T and 3 T using single‐shot GE‐EPI sequences. However, the specific echo‐time (TE) and repetition time (TR) varied between studies (Table S1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, three animal studies described changes in placental signal intensity during maternal hypoxia, normoxic hypercapnia and injection of a vasoconstrictor. Human studies were performed at both 1.5 T and 3 T using single‐shot GE‐EPI sequences. However, the specific echo‐time (TE) and repetition time (TR) varied between studies (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperoxic BOLD effect (ΔBOLD) in human pregnancies complicated by fetal growth restriction (FGR) . Three studies included FGR pregnancies, with FGR defined by low birth weight or low birth weight in combination with abnormal postnatal placental examination (Table S1). Initially, a small study including four FGR cases demonstrated inconsistent results regarding the hyperoxic BOLD effect.…”
Section: Introductionmentioning
confidence: 99%
“…Since the oxygen extraction by the fetus will always be greater than zero, a concentration gradient is always necessary, depending on the blood delivery conditions and blood velocity through the intervillous space. Deeper in the intervillous space the T2 of blood will be somewhere between arterial and venous saturation level as suggested by T2*‐weighted images of the placenta . Assuming that fetal oxygen extraction changes with gestational age, variations in the gradient of maternal blood saturation may influence our estimates of fetal blood saturation.…”
Section: Discussionmentioning
confidence: 99%
“…While this study focused on analyzing the temporal changes of blood oxygenation during maternal hyperoxia, Luo et al analyzed the spatiotemporal pattern of BOLD responses of the placenta to maternal hyperoxia, and found that the oxygen time-to-plateau of BOLD time course is significantly correlated with fetal brain volume and placental pathology [2]. The hemodynamic response was modeled as the convolution of a gamma function with the given oxygen paradigm.…”
Section: Introductionmentioning
confidence: 99%